Community action plans for social justice advocacy: Leveraging the relationship between awareness and action. Issue 4 (26th September 2020) - Braden, Sarah K.; Lund, Marie; Hatch, Katrina
Abstract: Supporting multilingual learners' access to equitable and socially just language education requires more from teachers than a critical stance and language awareness. Teachers of multilingual students must understand how their awareness and ideologies drive their actions and how their actions can generate new awareness both inside the classroom in pedagogical choices and outside the classroom in interactions with families and community partners. To aid teachers in moving through cycles of applying awareness to action, the authors designed the Community Action Plan (CAP) assignment for a family and community engagement course. This article outlines the components of the course curriculum and the conceptual framework that guided its design. The authors also provide a case study of how one novice teacher, Katrina (co‐author), navigated the curriculum. They offer suggestions for how language teacher educators might guide in‐service and preservice teachers to implement CAPs of various types to promote socially just language education for and with K–12 learners.